Transdisciplinary Policy in Handling COVID-19 in Indonesia: A Comparative Study on the Thought of Kuntowijoyo, M. Amin Abdullah and Yudian Wahyudi - Riyanto, Waryani Fajar; Saefudin; Suryo, Harsya Denny (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
This article explains how the Indonesian Government’s policies on handling the Covid-19 pandemic. Based on the Presidential Regulation of the Republic of Indonesia Number 82 Year 2020 concerning the Committee on Handling the Corona Virus Disease 2019 (Covid-19) and National Economic Recovery, Indonesia’s policy integrated health and economic strategies. The regulation adopted an interdisciplinary strategy moving towards multidisciplinarity in handling Covid-19 whereby both were deemed insufficient. The theoretical framework in this study applied Ken Wilber’s Universal Integralism or Holonic Integralism. This research employs the method of comparison of thinking. The present study establishes a transdisciplinary policy for handling Covid-19 in Indonesia with four strategies: subjective, objective, intersubjective, and interobjective. The researcher compares Indonesian Muslim thinkers on the four strategies models, namely Kuntowijoyo representing the subjective and objective strategy model, M. Amin Abdullah representing the intersubjective strategy model, and Yudian Wahyudi representing the inter-objective strategy model. This finding implies that the handling of Covid-19 in Indonesia will be more synergistic and interconnected between all sectors of human life.